Pengaruh Pendekatan Kontekstual Terhadap Hasil Belajar IPS - Weasni Nofiasri; Asiyah Asiyah; Desi Eka Citra Dewi (Indonesian Journal of Social Science Education (IJSSE), 2023)
This research is motivated by the problem of student learning outcomes which are still relatively low, this can be seen from the data on student scores in social studies subjects, there are still many who have not reached the minimum completeness criteria (KKM) score of 70. In the learning process the teacher acts as the only source information, where learning is only oriented or teacher centered (teacher centered approach). This makes social studies learning boring and makes students feel sluggish to learn so that it has an impact on student learning outcomes which can be seen from the average value of students in social studies subjects which still have not reached the minimum completeness criteria value limit (KKM). This type of research is quantitative research with an experimental approach. The population of this study was class VIII SMP Negeri 14 Seluma which amounted to 163 people and the sample in this study was class VIII.A, which amounted to 33 people. The data collection tool is a test (pre-test and post-test). The data analysis technique used paired t-test (paired t-test) for the effect of Contextual Teaching and Learning (CTL) on social studies learning outcomes. The result of this study is that there is an effect of using a contextual approach on social studies learning outcomes at SMP Negeri 14 Seluma. This can be seen from the test results tcount = 9.44 < ttable 5% = 2.036.